Інформаційна система аналізу груп складних видів дефектів ливарного виробництва для оперативного виявлення причин виникнення і визначення способів їх ліквідації - Мацулевич, Олександр Євгенович; Мацулевич, Александр Евгеньевич; Matsulevych, Oleksandr; Щербина, Віктор Михайлович; Щербина, Виктор Михайлович; Shcherbyna, Viktor; Малюта, Сергій Іванович; Малюта, Сергей Иванович; Maliuta, Serhii; Дмитрієв, Ю. О. (ТДАТУ, 2020)
Метою даної роботи є розробка тривимірної моделі ливарної форми для лиття під тиском з вдосконаленими вентиляційними каналами і ливникової системою для зниження пористості виливки. Для наочного представлення результатів роботи вірішені наступні завдання: – розроблено комп’ютерну тривимірну модель модель деталі «Корпус крана» в CAD системі Power Shape; – розроблено геометричну форму вентиляційного каналу літникової форми за допомогою CAD системи Power Shape; – розроблено ливарну форму із застосуванням модуля програми Power Shape. Целью данной работы является разработка трехмерной модели литейной формы для литья под давлением с усовершенствованными вентиляционными каналами и литниковой системой для снижения пористости отливки. Для наглядного представления результатов работы решены следующие задачи: - разработана компьютерная трехмерную модель модель детали «Корпус крана» в CAD системе Power Shape; - разработана геометрическая форма вентиляционного канала литейной формы с помощью CAD системы Power Shape; - разработана литейная форма с применением модуля программы Power Shape. At present, a progressive and widespread injection molding method is used as blanks for various parts. However, this process does not provide a guaranteed tightness of parts obtained by casting operations. Due to the increased gas-shrinkage porosity of the castings, the injection molding method is unable to ensure the quality of the working surfaces of the casting products. The existing methods of sealing with various sealants and impregnation in vacuum do not make it possible to obtain sealed detachable joints without defects. The appearance of a defect carries very valuable information about the nature of its occurrence and allows you to bring it to the right direction with sufficient accuracy when determining the causes of a marriage. The modern process of analyzing the causes of foundry defects and the development of means for their elimination is based solely on the experience of leading foundry specialists, most of whom are already of pre-retirement age, and «young» specialists lack professional experience. Therefore, it is extremely necessary to systematize the knowledge, skills and developments of leading specialists to analyze the causes of defects in the production of castings of body (and not only) parts made of cast iron and steel. The aim of this work is to develop a three-dimensional model of a casting mold for injection molding with improved ventilation channels and a gating system to reduce the porosity of the casting. For a visual presentation of the results of the work, the following tasks were solved: - a computer three-dimensional model of the «Crane body» part was developed in the Power Shape CAD system; - the geometric shape of the casting mold ventilation duct has been developed using the Power Shape CAD system; - a casting mold was developed using the Power Shape program module.
Информационная система анализа групп сложных видов дефектов литейного производства для оперативного выявления причин возникновения и определение способов их ликвидации
Information system for analysis of groups of difficult kinds of defects in casting production for rapid detection of the causes of occurrence and determination ways of their elimination
Keywords: тривимірна модель; ливарна форма; CAD система Power Shape; програмний модуль Toolmaker; літникова система; вентиляційний канал; еліптичний перетин; турбулентний рух потоку; трехмерная модель; литейная форма; программный модуль Toolmaker; литниковая система; вентиляционный канал; эллиптическое сечение; турбулентное движение потока; 3D model; casting mold; Power Shape CAD system; Toolmaker software module; gating system; ventilation duct; elliptical section; turbulent flow